Implications of incretin‐based therapies on cardiovascular disease. Issue 5 (1st November 2014) - Rotz, M. E.; Ganetsky, V. S.; Sen, S.; Thomas, T. F.
Summary: Background: Incretin‐based therapies offer another treatment option for patients with type 2 diabetes. Agents that provide glycaemic control in addition to attenuating cardiovascular disease (CVD) risk factors are important for diabetes management. This review will focus on the off‐target effects of incretin‐based therapies on CVD risk factors [body weight, blood pressure (BP), lipid profile and albuminuria], major adverse cardiovascular events (MACE), heart failure (HF) and beta‐cell preservation. Methods: A literature search was conducted to identify English‐language publications for incretin‐based therapies evaluating the following off‐target end‐points: body weight, BP, lipid profile, albuminuria, MACE, HF and beta‐cell function. Randomised controlled trials (RCTs) were prioritised as the primary source of information. Results: Overall, incretin‐based therapies have shown beneficial effects on CVD risk factors, and glucagon‐like peptide 1 (GLP‐1) receptor agonists appear to have a more pronounced effect compared with dipeptidyl peptidase‐4 inhibitors. RCTs are being conducted to determine if these positive effects on CVD risk factors translate to a reduction in MACE. To date, these studies have not shown an increase in MACE. A signal of increased hospitalisations for HF was observed with saxagliptin, warranting continued evaluation and vigilance in high‐risk patients. In addition, incretin‐based therapies have shown positive effects on measures of beta‐cell function supporting their durability in the management of diabetes. Conclusions: Incretin‐based therapies are an important treatment option for patients with type 2 diabetes, offering beneficial effects on CVD risk factors without increasing MACE.